1994
DOI: 10.1023/a:1018982125649
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The delivery of pharmaceuticals through the brain capillary endothelial wall, which makes up the blood-brain barrier (BBB) in vivo, may be facilitated by conjugation of therapeutics to brain drug delivery vectors. Since cationized albumin has been shown to undergo absorptive-mediated transcytosis through the BBB in vivo, cationized human serum albumin (cHSA) is a potential brain drug delivery vector in humans. Conjugation of biotinylated therapeutics to brain drug delivery vectors is facilitated by the prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…ingesting antigen-containing egg whites [71]. These facts support the idea that the novel avidin fusion proteins should not give rise to major immunological responses in vivo.…”
Section: The Potential Of Novel Avidin Fusion Proteins In Medical Tarsupporting
confidence: 64%
“…ingesting antigen-containing egg whites [71]. These facts support the idea that the novel avidin fusion proteins should not give rise to major immunological responses in vivo.…”
Section: The Potential Of Novel Avidin Fusion Proteins In Medical Tarsupporting
confidence: 64%
“…The brain volume of distribution (VD) of 1251-bio-PNA was determined from the ratio of dpm/g of brain divided by dpm/,tl of corresponding terminal plasma at 1 hr after injection. (17). In these experiments, 20 ,Ci of 1251-bio-PNA and 30 ,tg of OX26-SA conjugate were injected per rat.…”
Section: Methodsmentioning
confidence: 99%
“… 21 Endocytic pathways are activated within the cells using a directing moiety or a ligand, which is used as a vector. 22 It has recently been shown that glutathione is coupled with micelles and nanoparticles and showed enormous potential in both targeting and enhancing the drug moieties into brain. 23 …”
Section: Introductionmentioning
confidence: 99%